Funny turns in Young badminton player: A case of cerebellar infarction secondary to vertebral artery dissection - Shah, Bhupendra; Manandhar, Nawli; Paudel, Raju (Journal of Advances in Internal Medicine, 2021)
Spontaneous vertebral artery dissection is a rare cause of cerebellar infarction. Common presentations of cerebellar artery infarction are dizziness and ataxia. We are reporting a case of a 31-year-old male who presented with acute onset dizziness while playing badminton, who was diagnosed as cerebellar vermis infarction secondary to vertebral artery dissection.